2018
DOI: 10.1038/s41596-018-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of redox landscapes and dynamics in living cells and in vivo using genetically encoded fluorescent sensors

Abstract: Cellular oxidation-reduction reactions are mainly regulated by pyridine nucleotides (NADPH/NADP+ and NADH/NAD+), thiols and reactive oxygen species (ROS), and play central roles in cell metabolism, cellular signaling and cell fate decisions. A comprehensive evaluation or multiplex analysis of redox landscapes and dynamics in intact living cells is important for interrogating cell functions in both healthy and diseased states; however, until recently, this goal has been limited owing to the lack of a complete s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…The redox environment within the cell is spatially heterogeneous, which is evident from previous analyses using organelle-targeted redox sensors [20,36]. The mitochondrial intermembrane space is characterized by a higher redox potential relative to that in the cytosol and reflects mitochondrial activity involved in ROS generation [37].…”
Section: Discussionmentioning
confidence: 99%
“…The redox environment within the cell is spatially heterogeneous, which is evident from previous analyses using organelle-targeted redox sensors [20,36]. The mitochondrial intermembrane space is characterized by a higher redox potential relative to that in the cytosol and reflects mitochondrial activity involved in ROS generation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it can be adapted to high-throughput chemical screening of potential compounds targeting cellular metabolism in a variety of analytical platforms, including microplate readers, flow cytometry, fluorescence microscopy and high-content imaging systems. 97,654,[667][668][669][670][671][672][673][674] 31 P-magnetic resonance spectroscopy ( 31 P-MRS) methods 31 P-MRS based NAD + assay is a noninvasive method that could quantitatively measure intracellular NAD + contents and redox state in animal and human tissues, such as brains. It provides new approach to investigate intracellular NAD + redox state and metabolism in the human tissues with the potential for translation to human application.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Recently, Yang and colleagues showed that a highly responsive genetically encoded intracellular sensor, SoNar, can precisely report the changes of cytosolic NAD + and NADH redox states in real time, which is useful for the evaluation of glycolysis and mitochondrial respiration activities in cells . In the cytosol glycolysis produced NADH, which may be shuttled to mitochondria and oxidized, or recycled to NAD + by lactate dehydrogenase and produce lactate (Zou et al, 2018). The flux balance of these three pathways determines the cytosolic NADH/NAD + ratio.…”
Section: Introductionmentioning
confidence: 99%